Blundered Era Date on Coin of Arados, Civic Year 119 - Rowe, Martin (KOINON: The International Journal of Classical Numismatic Studies, 2018)
This paper details an unusual and intriguing bronze (Figure 1), struck by the Arados mint ca. 141-140 BC (civic year 119). It belongs to a group of coins more commonly known as Duyrat 2005, série 5. The well-established obverse and reverse iconography changed only marginally throughout the duration of this series, which lasted from ca. 206-51 BC (civic years 54-208). The longevity of série 5 suggests a certain degree of popularity; other types struck during the Hellenistic period were much shorter in duration.